Influência do enriquecimento ambiental no comportamento e desempenho de leitões na fase de creche - Oliveira, Marcus Vinicius Garcia de (2016)
The animal welfare assessment techniques are used to check the stress level of the animals. Swine production has been reported as one of the most stressful livestock. The nursery phase is heavily critical, whereas the piglets are liable to several agent stressors leading them to welfare state decrease and causing stereotyped behaviors. One way to reduce the issues stress in the nursery phase is environmental enrichment technique. This technique consists in providing enriching objects that stimulate the exploratory behavior pigs, increasing the well-being and animal cognition improvement. However, the enriching object pigs adaptation with permanent presence in pen leads to decreased of interaction frequency with the enriching object. Environmental enrichment in time intermittently may increase the piglets interaction frequency with enriching object, promoting the novelty aspect and increasing well-being. Therefore, the aim of the study was to evaluate the effect of time intermittently of environmental enrichment on the novelty effect and interaction frequency of piglets with enriching object (wheelbarrow tire) and its influence on the nursery piglets behavior and performance. Were used 720 piglets in nursery phase of both sexes. The piglets were assigned into four treatments: WEO - without enriching object; PEO - permanently enriching object; WEO24 - No enriching object with 24h intermittent; WEO48 - No enriching object with 48h intermittency. Were evaluated the piglets behavior whereof ethogram, the Black Globe and Humidity Index(BGHI) effect in the behavior, injury score, diarrhea score and performance. There was recorded a significant effect (p <0.05) in the piglets interaction with enriching object for treatments with intermittent time and A significant effect (p <0.05) of environmental enrichment treatments in reduce stereotypes behavior (WEO: 7.62%; PEO%: 6:21%; WEO24: 6,31%e WEO48: 6.59%). The BGHI variation changed the piglets behavior. Significant effects were observed (p <0.05) for lesion score values, diarrhea and performance among the treatments. The higher interaction frequency with the enriching object was observed in piglets submitted to, whereas was observed that the intermittency time promoted the novelty aspect when was reintroduced into the environment. The decreased stereotyped behavior increasing the piglets welfare. However, the intermittency time did not influence the piglets performance.